The effects of morning priming exercise on afternoon physical and cognitive performance in female field hockey players - Jamie Knight; Mark Russell; Daniel Cunningham; Natalie Brown; Christian Cook; Mark Waldron; Laura Mason; Liam Kilduff (PLoS ONE, 2026)
Objective Hockey players concurrently experience physical and cognitive fatigue during competition, yet these are critical for successful performance. Prior research has shown cognitive and physical impairments after hockey matches. Morning resistance training may enhance afternoon neuromuscular and cognitive performance via diurnal changes in hormonal status. This study aimed to examine the effects of morning resistance exercise on afternoon physical and cognitive performance in field hockey players . Methods On two separate occasions (randomised crossover design), 19 university female hockey players (19 ± 1 years) completed morning assessments of physical performance (countermovement jump, 40 m linear sprint) and cognitive function (rapid visual information processing, spatial working memory, paired associates of learning). Control (passive rest) or intervention (barbell back squat, 3 x 3 repetitions at 85% of one repetition maximum and barbell squat jump, 5 x 3 repetitions at 40% one repetition maximum) were implemented 5.5 h before afternoon assessments. Results Afternoon peak power output and jump height improved following intervention and control ( P < 0.05). Peak power output and jump height improvements were greater following intervention (7.46% and 13.52% respectively) relative to control (3.16% and 4.85% respectively). Cognitive and sprinting performance, and readiness to perform were unaffected by the intervention but did improve from morning to afternoon. Conclusion Morning lower-body heavy and ballistic resistance exercise enhanced afternoon physical performance markers but did not affect cognitive performance in female hockey players.